Functional Vision Questionnaire Detects Near Triad Impairments in Adolescent Athletes With Concussion History - Leinonen, Jouko (My University, 2024)
Concussions are mild traumatic brain injuries that often cause vision problems. They have significant impacts on everyday life, cognitive capacity, and sports performance, and may affect injury prevalence in fast contact sports such as ice hockey. A functional vision questionnaire specifically designed for sports was used here to study the correlation between vision problems and concussion history. In this national cross-sectional concussion study, 860 Finnish elite-level male adolescent ice hockey players (aged 13–21 years) answered a functional vision questionnaire and performed a computerized neurocognitive test, ImPACT. Totally 265 athletes reported a history of at least 1 concussion. Collected data was statistically compared with age-matched athletes with no concussion history (n = 595). For further analysis, athletes were divided into subgroups by age and number of previous concussions. Previously concussed athletes reported more general and eye-specific symptoms than their healthy controls. Increases in eye fatigue, frontal headaches, and blinking were statistically significant. Also significantly more problems with depth perception and evaluating distances, concentration problems, blurred vision, and losing the object in sight were observed among athletes with concussion history. Concussion history reflects an increase in the prevalence of vision deficits, as determined by multiple disturbances in the near triad. The significant number of vision problems in the concussion history groups strongly suggests that functional vision should routinely be evaluated in athletes. The vision problems observed in the athletes with concussion history may indicate an increased injury risk that should be addressed.
Keywords: Concussion, mild traumatic brain injury, sport vision, near triad, vision impairment